2013
DOI: 10.1080/00222895.2013.785928
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Balance Training on Cervical Sensorimotor Function and Neck Pain

Abstract: ABSTRACT. The authors' aim was to evaluate the effect of balance training on cervical joint position sense in people with subclinical neck pain. Thirty-four participants were randomly assigned to balance training or to stay active. Sensorimotor function was determined before and after 5 weeks of training by assessing the ability to reproduce the neutral head position and a predefined rotated head position. After balance training, the intervention group showed improved joint repositioning accuracy and decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 40 publications
0
29
0
2
Order By: Relevance
“…The close interaction of the cervical spine and postural control is also indicated by intervention studies showing, for instance, reduced postural sway after sensorimotor training of the cervical spine [44]. Complementarily, 5 weeks of balance training resulted in a positive effect on the sensorimotor function of the cervical spine assessed by head repositioning tasks [28]. The current data obtained in the dynamic perturbation task strengthen the close interaction of sensorimotor performance of the cervical spine and postural control: in neck pain patients, vibration decreased significantly the postural sway on an unstable support surface.…”
Section: Postural Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The close interaction of the cervical spine and postural control is also indicated by intervention studies showing, for instance, reduced postural sway after sensorimotor training of the cervical spine [44]. Complementarily, 5 weeks of balance training resulted in a positive effect on the sensorimotor function of the cervical spine assessed by head repositioning tasks [28]. The current data obtained in the dynamic perturbation task strengthen the close interaction of sensorimotor performance of the cervical spine and postural control: in neck pain patients, vibration decreased significantly the postural sway on an unstable support surface.…”
Section: Postural Controlmentioning
confidence: 99%
“…However, our findings reveal for the first time a positive effect of neck muscle vibration on impaired joint position sense acuity in patients with neck pain. For patients, different long-term treatments have previously been shown to improve repositioning accuracy: conscious head relocation tasks [26], chiropractic care [27], and balance training [28]. All these interventions took place over a period of several weeks.…”
Section: Joint Position Sensementioning
confidence: 99%
“…Such methods have been shown to be reliable(Michiels et al, 2013), successful in detecting improvements following intervention(Beinert and Taube, 2013; Reid et al, 2014), and able to discriminate between individuals with neck pain and asymptomatic controls(Chen and Treleaven, 2013; Descarreaux et al, 2010; Woodhouse and Vasseljen, 2008). While specific metrics, such as task error in the time domain, provide valuable information regarding subject performance, these measurements alone do not allow for inferences into system dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies compared mPrT effects on pain to inactive control groups [59,66,69,71] (Table 4). The Taimela study (low RoB) found significant reduction of neck pain [66] immediately after a 12-week multimodal intervention period, but not at the one-year follow-up measurement.…”
Section: Comparisons Iii: Mprt Versus Other Exercises Inactivity Ormentioning
confidence: 99%
“…Three major directions of PrT were identified. The interventions were described as (1) perceptive PrT (pPrT) where discriminatory perceptive exercises with somatosensory stimuli to the back and joint position sense is practiced [60,61], (2) as multimodal PrT (mPrT) postural control or balance exercises on labile surfaces often combined with other forms of exercise [59,[62][63][64][65][66][67][68][69][70][71][72][73], or as (3) head relocation PrT (rPrT) with head-eye coordination exercise [57,58,74].…”
Section: Interventionsmentioning
confidence: 99%